Sex-specific differences in antidepressant and antipsychotic treatment outcomes and serumlevels in children and adolescents - Scherf-Clavel, Maike; Fekete, Stefanie; Gerlach, Manfred; Correll, Christoph U.; Plener, Paul; Fegert, Jörg M.; Karwautz, Andreas; Heuschmann, Peter; Banaschewski, Tobias; Briegel, Wolfgang; Fleischhaker, Christian; Hellenschmidt, Tobias; et al. (Pharmaceutics, 2025)
Introduction: Sex-specific differences in psychopharmacological treatment have gained increasing attention in adults, with studies showing that women often have higher serum concentrations of psychotropic drugs due to biological differences. However, despite recognition of these differences in adults, reference ranges for therapeutic drug monitoring (TDM) in general, but even more sex-specific therapeutic windows for psychotropic drugs, are lacking in children and adolescents, who may metabolize and respond to medications differently. Aim: The study aimed to investigate sex-specific differences in antidepressant (AD) and antipsychotic (AP) -treatment outcomes, and pharmacokinetics in childhood/adolescence. In particular, we examined differences in AD and AP serum levels and clinical effects, including adverse drug effects (ADEs) and therapeutic effectiveness. Methods: This study is part of the multicenter “TDM-VIGIL” pharmacovigilance project, which prospectively followed patients aged 6-18 years treated with AD and AP across 18 child psychiatric centers in German-speaking countries from 2014 to 2018. Clinical data, including drug concentrations (AD: fluoxetine, mirtazapine, (es)citalopram, sertraline; AP: aripiprazole, quetiapine, olanzapine, risperidone), were collected using an internet-based registry, and treatment outcomes and ADEs were assessed during routine visits. Statistical analyses were performed to examine sex differences in pharmacokinetics and clinical responses, adjusting for age, weight, and other confounders. Results: A total of 705 patients (66.5% girls, 24.7% <14 years, mean age of 14.6 years) were included. Female patients were slightly older, had lower body weight, and were more often diagnosed with depression and anorexia nervosa, while boys were more frequently diagnosed with hyperkinetic disorders and atypical autism. We found no sex differences in the serum concentrations of investigated drugs when adjusted for age and weight. In fluoxetine treatment in patients diagnosed with mood (affective) disorders, female sex was associated with the probability for very good therapy response (p = 0.04), as well as with moderate treatment response (p = 0.02) compared to no treatment response. Discussion: Our findings suggest that sex may not affect serum levels of investigated AD and AP in children/adolescents. However, treatment outcome of fluoxetine was associated with sex, with higher probability for a better outcome in female patients diagnosed with mood (affective) disorders.
Gesehen am 13.11.2025